EVALUASI PENANGGULANGAN WELLCONTROL MENGUNAKAN DRILLER’S METHOD PADA TRAYEK 6-1/8” SUMUR “X” LAPANGAN “Y” - Sahmil Habibi Harahap; Nugroho Marsiyanto; Wahyu Sutresno (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2026)
This study evaluates the effectiveness of the application of the driller's method on the 6-1/8